The role of immunity to mosquito salivary proteins in the pathogenesis of flaviviruses (Flavivirus:Flaviviridae) - Machain Williams, Carlos Ignacio, author; Blair, Carol D., advisor; Beaty, Barry J., committee member; Bowen, R. A., committee member; Olson, Kenneth E., committee member; Zeidner, Nordin, committee member (Colorado State University. Libraries, 2007)
Mosquito salivary proteins (MSP) have been implicated in the enhancement of arthropod-borne virus pathogenesis. Dengue viruses (DENV) are emerging pathogens transmitted mainly by Aedes aegypti mosquitoes. West Nile virus (WNV) is also considered an emerging pathogen that recently has been introduced into the Western Hemisphere. WNV is transmitted by mosquitoes from Culex species. Mosquito salivary proteins were obtained by a novel technique involving collection in a salivation buffer and concentration by trichloroacetic acid (TCA) precipitation. Immunoreactive proteins from Cx. tarsalis and Ae. aegypti were proposed to be related to viral pathogenesis. In a retrospective study in Thai patients who had DENV2 secondary infections with disease severity ranging from dengue fever (DF) to dengue hemorrhagic fever (DHF), it was found that the proportion of patients with DF who had antibodies reacting against the 36 kDa Ae. aegypti MSP (71.4%) was significantly higher compared to those who had DHF (62%). In contrast, a higher proportion (36%) of DHF patients reacted to an Ae. aegypti protein identified as apyrase than those with anti-apyrase antibodies presenting with DF (14.3%). To investigate the potential role of immune response to MSP in virus pathogenesis, NIH-Swiss mice were immunized with Cx. tarsalis mosquito salivary gland homogenates followed by challenge by WNV-infected mosquitoes. In vaccinated mice, viremia was first detected by RT-PCR 48 hours after mosquito bite; in contrast, the unvaccinated control group presented viremia as early as 24 hours after mosquito challenge. WNV RNA was detected in brains of unvaccinated mice at day four post challenge; in contrast no viral RNA was detected by RT-PCR in the brains of vaccinated mice by day four. By day eight post challenge all the mice had viral RNA in their brains detectable by RT-PCR. The anti-WNV antibody titers were also higher in the vaccinated group than in unvaccinated mice (P<0.0008). When Th1/Th2 specific cytokines were analyzed by Q-RT-PCR, IL-2, IFNγ and TNFα were increased in the vaccinated group. In contrast, IL-4 was up-regulated in the unvaccinated group.
Keywords: pathology; virology; immunology